Sektor państwowy w rozwiniętych krajach kapitalistycznych - Nowicki, Józef (Wydział Prawa i Administracji UAM, 1976)
In economic activity of c a p i t a l i s t i c state, a rapid growth of government production sector as a new element liais become after World War II. The main object of creation of an institution is — similarly to older forms of state interference — guarantee and strengthen power of the ruling class. Analysis of concrete tasks and instruments of government sector economic policy leads to the following conclusions: — growth dynamics of government sector is relatively important, but his influence on reduction of privilege in economic activity of private corporations is imperceptible; — price policy in government sector lis like to carry on by private corporations; — government sector investment policy is an important element Of economic development strategy for all economy; — government production sector activity brings many goals for private corporations.
Government Sector in Developed Capitalist Countris